Author Correction: Synthetic RNA-based logic computation in mammalian cells - Satoshi Matsuura (Nature Portfolio, 2019)
The original version of this Article contained an error in the fourth sentence of the second paragraph of the ‘Improving the performance of miRNA-responsive circuits’ section of the Results, which incorrectly read ‘We confirmed a significant fold-change between ON and OFF states (from 3.5- to 9.0-fold) in 293FT cells (Supplementary Figure 3).’ The correct version states ‘4.6’ in place of ‘3.5’. This has been corrected in both the PDF and HTML versions of the Article. The original version of the Supplementary Information contained a corresponding error in Supplementary Figure 3. The HTML has been updated to include a corrected version of the Supplementary Information.